Implementation of Speech Tactics of Persuasion Strategy in Virtual Communication during COVID-19 Pandemic: Communication Moves - O. Yu. Gukosyants (Научный диалог, 2023)
The communicative moves are analyzed, through which tactics of persuasion strategy are implemented: the tactics of referring to authority, the tactics of reasoning / persuasion and the tactics of a negative scenario. The study was conducted on the material of more than 150 threads of comments on LiveJournal posts, which are examples of the implementation of these tactics, published during the COVID-19 pandemic and selected by a continuous sample. The main research methods were the methods of linguo-stylistic, pragmalinguistic and contextual analysis, descriptive and comparative methods. It is concluded that the tactics of referring to authority are characterized by a communicative course of mentioning an authoritative person, a communicative course of clarification, demonstration of one’s own awareness, a communicative course of comparison / alignment; the tactics of reasoning / persuasion was achieved through the use of a communicative course of demonstrating the irrefutability of conclusions, a communicative course of expressing an assumption; the tactics of the negative scenario were embodied in the communicative moves of deceived expectations and the prediction of the apocalypse.